Subjects and simulations : between Baudrillard and Lacoue-Labarthe - O'Byrne, Anne E. (Anne Elizabeth), 1966-; Silverman, Hugh J. (Lexington Books, 2014)
Subjects and Simulations presents essays focused on suffering and sublimity, representation and subjectivity, and the relation of truth and appearance through engagement with the legacies of Jean Baudrillard and Philippe Lacoue-Labarthe.